PERUBAHAN FONOLOGIS DAN MORFOLOGIS KATA SERAPAN SUNDA DARI AL-QUR’AN DAN PEMANFAATANNYA DALAM PEMBELAJARAN BAHASA ARAB - Irawan, Rudi (Departemen Pendidikan Bahasa Arab, 2020)
Islam came to brought a major contribution to develop society. Among them, enrichment of words absorption from the Al-Qur’an. This is provied by the strong relationship since Islam entered Sunda. This study aims to find out the phonological, and morphological changes of their, and also to determine the method of their use in teaching Arabic. Researcher used a descriptive analysis method. The way to compare the two languages, between Arabic and Sundanese, using two dictionaries. Then describe and analyze them, and try to apply them in teaching Arabic. The results showed changes in them in terms of phonological, which is divided into four: sound removal, sound impairment, addition of sounds and changes in sound, and morphological which can take the form of masdar changes into fa'il, mufrad-jama', jama'-mufrad, Masdar-another masdar, and the addition of morpheme. This research also shows that they can be utilized in teaching Arabic.